Gap junctional intercellular communication and endoplasmic reticulum stress regulate chronic cadmium exposure induced apoptosis in HK-2 cells. (15th May 2018) - Ge, Zehe; Diao, Haipeng; Ji, Xiaoli; Liu, Qingping; Zhang, Xiaoyan; Wu, Qing
Highlights: Prolonged exposure to a non-lethal dose of CdCl2 induces apoptosis in HK-2 cells. Activation of AKT at the early stage is an adaptive response during prolonged Cd exposure. Prolonged Cd treatment induces ER stress, increases GJIC levels, and inactivates AKT. IRE1α-ASK1 pathway is involved in prolonged Cd-treatment-induced apoptosis. AKT signaling, ER stress and GJIC collaboratively regulate Cd-induced toxicity. Abstract: Cadmium (Cd), a toxic heavy metal, is known to induce renal toxicity by primarily targeting at renal proximal tubule. Endoplasmic reticulum (ER) stress and gap junctional intercellular communication (GJIC) regulate many pathophysiological processes. Yet, how ER stress and GJIC regulate Cd-induced nephrotoxicity remain elusive. In this study, we treated human proximal tubule (HK-2) cells with 1 μM CdCl2 every other day for 12 days and found that Cd significantly increased cell apoptosis at 10 and 12 days. This cytotoxicity correlated with activation of ER stress and apoptotic signaling evidenced by upregulation of inositol-requiring enzyme 1 (IRE1α), splice X-box binding protein-1 (XBP-1s), and apoptosis signal-regulating kinase 1 (ASK1) proteins. Interestingly, the AKT signaling was activated at 2- and 4-day and then inhibited at 10- and 12-day of Cd treatment; by contrast, Cd decreased GJIC levels at 2- and 4-day followed by a significant increase at 10- and 12-day treatment. Activation of AKT by SC79 or inhibition of GJIC by 18α-glycyrrhetinic acid (18α-GA) completely abolished Cd-induced AKT inhibition and IRE1α-ASK1 activation. Importantly, pretreatment with ER stress inhibitor or 18α-GA significantly mitigated Cd-induced apoptosis. These results suggest that GJIC collaborates with AKT signaling and ER stress in regulating prolonged Cd-treatment-induced apoptosis in HK-2 cells.